THE ROLE OF PROMOTIONAL GIMMICKS WITH 10% DISCOUNT ON PURCHASE DECISIONS FOR WARDAH WHITE SECRET PRODUCTS AT MISS GLAM STORE IN BENGKULU CITY - Sauci Rahmadea Putri; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
The use of promotional gimmicks, such as price discounts, is one of the effective marketing strategies in encouraging consumer purchasing decisions. This study aims to analyze the role of promotional gimmicks in the form of a 10% price discount on the decision to provide Wardah White Secret products at the Miss Glam Store in Bengkulu City. The method used is a thematic literature review, referring to various studies related to the influence of price promotions on consumer behavior in the cosmetics sector. The results of the study show that a 10% price discount significantly increases consumer attraction to the product, creates a higher perception of value, and encourages faster purchasing decisions. In addition, this promotion also strengthens the competitiveness of Wardah White Secret products in the local market. However, the effectiveness of this promotional gimmick is also influenced by external factors, such as brand loyalty, product quality, and the marketing communication strategy used. This study provides insight for cosmetic business actors, especially at the Miss Glam Store, to maximize the implementation of promotional gimmicks in supporting increased sales and consumer satisfaction.